Alternative Social Security Systems in CIS Countries - Ahmad, Ehtisham; Schneider, Jean-Luc. (Washington, D.C. : International Monetary Fund, 1993)
In the USSR in 1990, social security reforms led to the imposition of a uniform system of benefits in a large and demographically diverse country. This required inter-regional transfers, which are now no longer feasible with the demise of the USSR. Relatively high contribution rates also pose a problem for a nascent commercialized sector. The paper argues that benefit levels in some former Soviet Union countries are now unsustainable. The price shock associated with the 'transition' to a market economy should lead to a consideration of a 'mix' of policies, including a basic benefit in kind. While funded systems may eventually reduce contribution rates, there are implementation difficulties in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet